The Composition of Sense in Gertrude Stein's Landscape Writing - Voris, Linda; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
This book offers a bold critical method for reading Gertrude Stein's work on its own terms by forgoing conventional explanation and adopting Stein's radical approach to meaning and knowledge. Inspired by the immanence of landscape, both of Provence where she travelled in the 1920s and the spatial relations of landscape painting, Stein presents a new model of meaning whereby making sense is an activity distributed in a text and across successive texts. From love poetry, to plays and portraiture, Linda Voris offers close readings of Stein's most anthologized and less known writing in a case study of a new method of interpretation. By practicing Stein's innovative means of making sense, Voris reveals the excitement of her discoveries and the startling implications for knowledge, identity, and intimacy.
Introduction: The Force of Landscape -- Chapter 1. Making Sense: Stein's Radical Epistemology -- Chapter 2. Taking Place in Love Poems -- Chapter 3. Framing Space: The First Landscape Play -- Chapter 4. Dissolving the Frame -- Chapter 5. Portraiture after Landscape -- Conclusion: Relating Chance and Choice.
Keywords: Literature, Modern-20th century; Poetry and Poetics